Dynamic regulation of semaphorin 7A and adhesion receptors in ovarian follicle remodeling and ovulation - Emery, Alaknanda; Dunning, Kylie R.; Dinh, Doan T.; Akison, Lisa K.; Robker, Rebecca L.; Russell, Darryl L. (Frontiers in Cell and Developmental Biology, 2023)
The ovarian follicle is a complex structure that protects and helps in the maturation of the oocyte, and then releases it through the controlled molecular and structural remodeling process of ovulation. The progesterone receptor (PGR) has been shown to be essential in regulating ovulation-related gene expression changes. In this study, we found disrupted expression of the cellular adhesion receptor gene Sema7A in the granulosa cells of PGR−/− mice during ovulation. We subsequently found that expression of Sema7A in preovulatory follicles is promoted by gonadotropins and hypoxia, establishing an asymmetrical pattern with the SEMA7A protein enriched at the apex of large antral follicles. Sema7A expression was downregulated through a PGR-dependent mechanism in the periovulatory period, the abundance of SEMA7A protein was reduced, and the asymmetric pattern became more homogeneous after an ovulatory stimulus. Receptors for Sema7A can either repel or promote intercellular adhesion. During ovulation, striking inverse regulation of repulsive Plxnc1 and adhesive Itga5/Itgb1 receptors likely contributes to dramatic tissue remodeling. The adhesive receptor Itga5 was significantly increased in periovulatory granulosa cells and cumulus–oocyte complexes (COCs), and functional assays showed that periovulatory granulosa cells and COCs acquire increased adhesive phenotypes, while Sema7A repels granulosa cell contact. These findings suggest that the regulation of Sema7A and its associated receptors, along with the modulation of integrin α5, may be critical in establishing the multilaminar ovarian follicle structure and facilitating the remodeling and apical release of the cumulus–oocyte complex during ovulation.